No time to die: An in-depth analysis of James Bond's exposure to infectious agents. Issue 44 (November 2021) - Graumans, Wouter; Stone, William J.R.; Bousema, Teun
Abstract: Global travelers, whether tourists or secret agents, are exposed to a smörgåsbord of infectious agents. We hypothesized that agents pre-occupied with espionage and counterterrorism may, at their peril, fail to correctly prioritize travel medicine. To examine our hypothesis, we examined adherence to international travel advice during the 86 international journeys that James Bond was observed to undertake in feature films spanning 1962–2021. Scrutinizing these missions involved ∼3113 min of evening hours per author that could easily have been spent on more pressing societal issues. We uncovered above-average sexual activity, often without sufficient time for an exchange of sexual history, with a remarkably high mortality among Bond's sexual partners (27.1; 95% confidence interval 16.4–40.3). Given how inopportune a bout of diarrhea would be in the midst of world-saving action, it is striking that Bond is seen washing his hands on only two occasions, despite numerous exposures to foodborne pathogens. We hypothesize that his foolhardy courage, sometimes purposefully eliciting life-threatening situations, might even be a consequence of Toxoplasmosis . Bond's approach to vector-borne diseases and neglected tropical diseases is erratic, sometimes following travel advice to the letter, but more often dwelling on the side of complete ignorance. Given the limited time Bond receives to prepare for missions, we urgently ask his employer MI6 to take its responsibility seriously. We only live once.